Optimalisasi Diversifikasi Produk Olahan Ubi Kayu Untuk Mendukung Ketahanan Pangan Lokal Di Lampung - Tohairul Anam; Erlin Kurniati (SUAN PUBLISHER, 2025)
Cassava (manihot esculenta) is one of the leading commodities in Lampung Province which has great potential to be developed as a local food source. However, its use is still dominated by conventional forms of consumption such as cassava and boiled cassava, without any further processing that can increase the added value. This study aims to analyze the optimization strategy of diversification of cassava processed products to support local food security in Lampung. The method used is a qualitative approach with data collection techniques through observation, in-depth interviews with farmers, micro-enterprises, and Related Agencies, and documentation. The results showed that the diversification of processed products such as mocaf flour, chips, instant tiwul, and fermented products has a great opportunity to strengthen food security because it is durable, nutritious, and adaptive to market tastes. The constraints faced include the limitation of processing technology, lack of skills training, and market access that has not been optimal. Therefore, there is a need for synergy between local governments, business actors, and educational institutions in terms of food technology innovation, strengthening the capacity of business actors, and developing marketing networks. Optimizing the diversification of cassava products not only supports food security, but also contributes to the economic empowerment of rural communities in Lampung